Constitutively‐expressed and induced immune effectors in the house fly (Musca domestica) and the transcription factors that may regulate them. Issue 6 (5th August 2022) - Asgari, Danial; Saski, Christopher A.; Meisel, Richard P.; Nayduch, Dana
Abstract: Insects possess both infection‐induced and constitutively expressed innate immune defences. Some effectors, such as lysozymes and antimicrobial peptides (AMPs), are constitutively expressed in flies, but expression patterns vary across tissues and species. The house fly ( Musca domestica L.) has an impressive immune repertoire, with more effector genes than any other flies. We used RNA‐seq to explore both constitutive and induced expression of immune effectors in flies. House flies were fed either Pseudomonas aeruginosa or Escherichia coli, or sterile control broth, and gene expression in the gut and carcass was analysed 4 h post‐feeding. Flies fed either bacterium did not induce AMP expression, but some lysozyme and AMP genes were constitutively expressed. Prior transcriptome data from flies injected with bacteria also were analysed, and these constitutively expressed genes differed from those induced by bacterial injection. Binding sites for the transcription factor Myc were enriched upstream of constitutively expressed AMP genes, while upstream regions of induced AMPs were enriched for NF‐κB binding sites resembling those of the Imd‐responsive transcription factor Relish. Therefore, we identified at least two expression repertoires for AMPs in the house fly: constitutively expressed genes that may be regulated by Myc, and induced AMPs likely regulated by Relish. Abstract : We determined that there are two groups of antimicrobial peptide (AMP) genes in house fly. One group is highly constitutively expressed, and the other is induced upon infection. Binding sites of the transcription factor Myc are enriched upstream of highly constitutively expressed AMP genes. Myc regulates cellular growth, suggesting it has been coopted for immune genes. We found enrichment of Imd‐responsive (NF‐κB) motifs upstream of induced AMP genes, consistent with how the Imd pathway regulates induced AMP expression in Drosophila .